Archaeologies of text : archaeology, technology and ethics - Rutz, Matthew; Kersel, Morag M., 1964- (Joukowsky Institute publication, 2014)
"Examining the archaeology-text nexus from multiple perspectives, contributors to this volume discuss current theoretical and practical problems that have grown out of their work at the boundary of the division between archaeology and the study of early inscriptions. In 12 representative case-studies drawn from research in Asia, Africa, the Mediterranean, and Mesoamerica, scholars use various lenses to critically examine the interface between archaeology and the study of ancient texts, rethink the fragmentation of their various specialized disciplines, and illustrate the best in current approaches to contextual analysis"--Provided by publisher.